Corporate Mining and Sustainability: Assessing the Socioeconomic effects of Mining on Pastoral Community in Hazara District - Nasruminullah; Ahmad Haris (Social Science Review Archives, 2025)
Mining has severely impacted the livelihoods of pastoral communities by degrading grazing lands, depleting water sources and reducing livestock productivity that directly affects household income and livelihoods. This study explores perception of pastoral community towards the effects of mining on their livelihood in District Hazara with objectives: to investigate the effects of mining on traditional land use patterns of pastoral communities, to investigate the economic effects consequences of mining activities of Hazara district, and analyze the effects of mining on livestock and pasture resources. The universe of study is district Hazara by using qualitative research method used in which text extracted from discussion with ethnographic approach to deeply understand the pastoral community perception. The method for gathering data is an in-depth interview where qualitative research technique (interview guide) involves. Initially 20 respondents are selected from pastoral community in the study area for in-depth interviews that can be expanded based on non-saturation. Convenience sampling is employed to select respondents based on their accessibility and availability while bases on thematic analysis technique data was analyze. Studies show that mining activities lead to extensive deforestation, land degradation, and soil contamination, which significantly reduce the availability and quality of grazing lands. The depletion of natural vegetation forces livestock to rely on nutrient-deficient pastures, leading to malnutrition, reduced fertility, and lower milk and meat yields. Mining operations require large amounts of water, often leading to the depletion of traditional water sources such as wells, springs, and rivers. With livestock suffering from poor nutrition and disease, their market value declines significantly. Research findings suggest that pastoralists are increasingly forced into distress sales, selling animals at unfavorable prices to meet household expenses. As traditional pastoralist livelihoods become unsustainable, many community members are compelled to seek alternative income sources, such as wage labor, small-scale trade, or migration to urban areas. However, research indicates that these alternatives often provide lower and less stable incomes, leaving former pastoralists vulnerable to poverty and exploitation.